Implementasi Kurikulum 2013 di SMA Islam Al-Azhar 9 Yogyakarta - Khusnul Khotimah (STAI Terpadu Yogyakarta, 2019)
Curriculum of 2013 demands that in the implementation of learning students are given the freedom of thinking to understand problems, develop problem solving strategies, propose ideas freely and openly. The teacher's activity in learning is to train and guide students to think critically and creatively in solving problems. The teacher must strive to organize cooperation in study groups, train students to communicate using graphs, diagrams, schemes, and variables. It is expected that the entire work is always presented in front of the class to find various concepts, results of problem solving, rules and principles found through the learning process. Learning is not only emphasized on one aspect, but the balance on the affective aspects, psychomotor aspects, and cognitive aspects.